A feasibility study: use of actigraph to monitor and follow‐up sleep/wake patterns in individuals attending community pharmacy with sleeping disorders. - Mohamad Noor, Zaswiza; Smith, Alesha J.; Smith, Simon S.; Nissen, Lisa M. (Medknow Publications and Media Pvt. Ltd, 2016)
Introduction: Community pharmacists are in a suitable position to give advice and provide appropriate services related to sleep disorders to individuals who are unable to easily access sleep clinics. An intervention with proper objective measure can be used by the pharmacist to assist in consultation. Objectives: The study objectives are to evaluate: (1) The effectiveness of a community pharmacy‐based intervention in managing sleep disorders and (2) the role of actigraph as an objective measure to monitor and follow‐up individuals with sleeping disorders. Methods and Instruments: The intervention care group (ICG) completed questionnaires to assess sleep scale scores (Epworth Sleepiness Scale [ESS] and Insomnia Severity Index [ISI]), wore a wrist actigraph, and completed a sleep diary. Sleep parameters (sleep efficiency in percentage [SE%], total sleep time, sleep onset latency, and number of nocturnal awakenings) from actigraphy sleep report were used for consultation and to validate sleep diary. The usual care group (UCG) completed similar questionnaires but received standard care. Results: Pre‐ and post‐mean scores for sleep scales and sleep parameters were compared between and within groups. A significant difference was observed when comparing pre‐ and post‐mean scores for ISI in the ICG, but not for ESS. For SE%, an increase was found in the number of subjects rated as “good sleepers” at post‐assessment in the ICG. Conclusions: ISI scores offer insights into the development of a community pharmacy‐based intervention for sleeping disorders, particularly in those with symptoms of insomnia. It also demonstrates that actigraph could provide objective sleep/wake data to assist community pharmacists during the consultation.